2022
DOI: 10.1111/iwj.13966
|View full text |Cite
|
Sign up to set email alerts
|

The association of wound factors and symptoms of fatigue and pain with wound healing in chronic venous leg ulcers

Abstract: The purpose of this study was: (1) to characterise the association of wound area, wound exudate C‐reactive protein (CRP), broad‐spectrum matrix metalloprotease protein (MMPs), and symptoms of fatigue and pain in individuals with chronic venous leg ulcers (CVLUs) over time and (2) to identify factors associated with the wound healing trajectory in CVLUs. Seventy four participants with CVLU who received weekly sharp debridement were recruited from a wound care clinic during the 8‐week study period. To examine as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Activated macrophages, as the primary producers of proinflammatory cytokines that contribute to the activation of inflammatory reactions [51], play a crucial role in the development of pain in chronic VLU patients. Studies have shown the involvement of specific pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, in the pathogenesis of pain in these patients [51,56].…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…Activated macrophages, as the primary producers of proinflammatory cytokines that contribute to the activation of inflammatory reactions [51], play a crucial role in the development of pain in chronic VLU patients. Studies have shown the involvement of specific pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, in the pathogenesis of pain in these patients [51,56].…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…According to recent data, the global prevalence of diabetes in 2021 is estimated at approximately 537 million individuals. Projections indicate that this figure is anticipated to rise to 643 million by 2030 and further increase to 783 million by 2045 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several international studies refer to the ulcers as chronic leg ulcers (Bergqvist et al, 1999;Kelechi et al, 2021;Kim et al, 2023;Lee et al, 2022;Meulendijks et al, 2020;Probst et al, 2021). However, chronic ulcers encompass ulcers of any origin that do not heal within a month (Sen, 2019), three months (Martin & Nunan, 2015), or six weeks (RiksSår, 2021).…”
Section: Venous Leg Ulcersmentioning
confidence: 99%